Analisis Gaya Belajar Anak Usia Sekolah Dasar di SDN 19 Nan Sabaris (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
Learning styles play an important role in influencing how students receive learning provided by teachers. This study aims to identify students' learning styles during the learning process at the elementary school level. Using a qualitative approach, this study describes and explains the variations in students' learning styles. The results of the study showed that students in grade IV of SDN 19 Nan Sabaris have various learning styles, where 21.43% of students discuss auditory learning styles, 64.29% visual learning styles, and 11.29% kinesthetic learning styles. From these results, it can be concluded that the most dominant learning style is the visual learning style, which shows that students find it easier to understand learning materials through what they see compared to what they hear. Therefore, it is important for teachers to understand students' learning styles in order to determine the right strategies and media in learning activities. In addition, parents are also expected to be able to create a conducive learning environment according to the needs of their children, so that the learning process becomes more effective.